1996
DOI: 10.1002/(sici)1097-4644(19960301)60:3<387::aid-jcb10>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of insulin-like growth factor binding protein-1 kinases from human hepatoma cells

Abstract: The phosphorylation of insulin-like growth factor binding protein-I (IGFBP-1) alters its binding affinity for insulin-like growth factor I (IGF-I) and thus regulates the bioavailability of IGF-I for binding to the IGF-I receptor. The kinase(s) responsible for the phosphorylation of IGFBP-1 has not been identified. This study was designed to characterize the IGFBP-1 kinase activity in HepG2 human hepatoma cells, a cell line that secretes IGFBP-1 primarily as phosphorylated isoforms. IGFBP-1 kinase activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Lithium has an effect, albeit less potently, on protein kinases other than GSK3 (Davies et al, 2000), including casein kinase 2, which can phosphorylate IGFBP-1 (Ankrapp et al, 1996). In Figure 3(inset) we show that the pattern of isoforms of IGFBP-1 seen on immunoblotting after native PAGE are not changed by 10 mM lithium chloride.…”
Section: T-test)mentioning
confidence: 87%
“…Lithium has an effect, albeit less potently, on protein kinases other than GSK3 (Davies et al, 2000), including casein kinase 2, which can phosphorylate IGFBP-1 (Ankrapp et al, 1996). In Figure 3(inset) we show that the pattern of isoforms of IGFBP-1 seen on immunoblotting after native PAGE are not changed by 10 mM lithium chloride.…”
Section: T-test)mentioning
confidence: 87%
“…Because both IGFBP-1 and IGFBP-3 are phosphorylated at central domain residues close to the cysteine-rich N-terminal domain, and the kinases involved were considered likely to be CK1, CK2, or a related enzyme (26,31), we also considered whether CK2 might phosphorylate IGFBP-5. Ser 96 was predicted as a potential CK2 phosphorylation site by the kinase specificity prediction program NetPhosK 1.0, and we observed that DRB, a specific inhibitor of CK2, reduced 32 P incorporation into IGFBP-5 in cellular metabolic labeling experiments.…”
Section: Discussionmentioning
confidence: 99%
“…1991;Koistinen et al 1993a, b). CK2 modulates IGF-I activity in vitro based on the finding that it phosphorylates IGFBP-1 in HepG2 (Ankrapp et al 1996) and decidual cells (Frost and Tseng. 1991 LC-MS analysis of IGFBP-1 phosphopepƟde peak intensity raƟos calculated from the relaƟve phosphopepƟde peak intensiƟes between the control and FGR groups N-terminal C-terminal Linker region P P P P Ser101 S119 S169…”
Section: Igfbp-1 Phosphorylation In Fgrmentioning
confidence: 99%